Five nights at Freddy's. Tales from the pizzaplex : graphic novel collection. Vol. 1 - Cawthon, Scott, 1971-; Waggener, Andrea Rains, 1960-; Hastings, Chris, 1983- (Cawthon, Scott, 1971- Five nights at Freddy's. Tales from the pizzaplex, 2025)
Have you ever ignored your conscience and done something you really knew you shouldn't...? Maya can't resist the temptation to explore an under construction section of Freddy Fazbear's Mega Pizzaplex... Aiden and Jace decide to scare some young kids in the Tube Maze of the Pizzaplex... and Fazbear technician Grady doesn't listen to the voice in his head telling him to stay away from small, cramped places when doing his safety checks... In this volume, three stories from the Publishers Weekly bestselling series Five Nights at Freddy's: Tales from the Pizzaplex come to life in delightfully horrifying comics. Readers beware: This collection of terrifying tales is enough to unsettle even the most hardened Five Nights at Freddy's fans...